ANALISIS PELESTARIAN FOLKLOR REMAJA PADA MOTIF BATIK (STUDI KASUS PERKEMBANGAN MOTIF BATIK DI SURAKARTA) - Renzi Noviana; Indah Puspitasari; Omy Marissa Verdiani; Ninik Nitasari; Mohamad Rizki Azhar; Maria Reginatasya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Batik is a handicraft that has a variety of motifs with a philosophy. Batik motifs have experienced rapid development adapting to the times. In an effort to preserve batik, there needs to be involvement of various parties, especially teenagers or millennials. Our findings show that there is a problem, namely the lack of attention or awareness of teenagers towards batik as a cultural symbol, especially the philosophy of the batik motif itself. The aim of this research is to analyze the strengthening of local cultural values ​​among teenagers through preserving youth folklore in batik motifs and providing an understanding of the philosophy of batik motifs. This research was conducted in Surakarta, namely in Kampung Batik Laweyan, precisely at Batik Mahkota Laweyan, and Kampung Batik Kauman, precisely in Batik Gunawan Setiawan. The research method used is a qualitative research method with a case study approach. The research results show that there are different characteristics in the two batik industries, where Batik Mahkota Laweyan focuses on developing contemporary motifs while Batik Gunawan Setiawan focuses on preserving traditional motifs. In this case, there are several considerations for teenagers when choosing batik, including contemporary motifs, calm coloring, and simple clothing styles. The classification of batik motifs that are in accordance with the characteristics of youth folklore includes the Sidomukti motif, Parang motif, Truntum motif, Satrio Manah motif, Semen Rante motif, Wahyu Tumurun motif, Wirasat motif, Pisang Bali motif, as well as the Millennial motif which includes the Maestro and Maestro Super motifs.